The Effect of Oketani Massage on Increasing The Frequency of Breastfeeding of Postpartum Mothers - Della, Della Yuliza; Puspita Haryanti, Richta; Amalia, Amalia (Global Indonesia Health Care (GOICARE), 2025)
Background: Breastfeeding is essential for infant growth and development. However, various challenges such as nipple pain, mastitis, and poor milk flow often hinder postpartum mothers from breastfeeding optimally. Oketani massage has been proposed as a method to enhance breast milk production by stimulating the pectoralis muscle. Purpose: This study aimed to evaluate the effect of Oketani massage on increasing the frequency of breastfeeding among postpartum mothers in Bandar Lampung, Indonesia. Methods: A pre-experimental one-group pretest-posttest design was conducted with 28 postpartum mothers at the Wede Arrachman Primary and Maternity Clinic in 2024. Participants received Oketani massage twice daily for 10–15 minutes. Breastfeeding frequency was assessed before and after the intervention using structured questionnaires. Data were analyzed using the Shapiro-Wilk and paired t-test. Results: Prior to the intervention, all participants (100%) experienced non-fluent breastfeeding. Post-intervention, 78.57% reported improved milk flow and increased feeding frequency (p-value = 0.000). The mean increase in breastfeeding frequency demonstrated statistically significant improvement. Conclusion: Oketani massage significantly improves breastfeeding frequency among postpartum mothers. It is recommended as a non-pharmacological intervention to enhance lactation and support exclusive breastfeeding practices.